DIFFERENT VIEWS OF CRIMINAL PUNISHMENTS : (The analysis of the laws of foreign countries) - Ruzikul o‘g‘li, Buronov Shahboz (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2024)
Abstract: In the present paper explains the system of criminal penalties in the legislation of foreign states. The subject of journalistic research supports the complex theoretical and practical problems of systematization of types of punishment, their implementation and the effectiveness of foreign criminal legal theory, legislation and law enforcement practice.